دور المؤسسات الأهىية الخاصة في إفريقيا - فاغنر أنموذجا - سعد جمال (جامعة المسيلة, 2025)
This study aims to clarify the nature of military and security companies, as they have come to occupy a special place in today's military conflicts. Their presence, particularly in conflict zones in Africa, represents a turning point that has changed many aspects of military conflict on the ground, especially with the significant increase in the size and armament of these forces, the increase in the number of their personnel, and their capabilities, which now exceed those of entire countries. It also aims to clarify the legal description that can be given to their employees and to understand their objectives, with a case study of one of these companies, the Russian Wagner Group, and the extent of its influence on the conflict in Africa, along with the repercussions and changes it has had on the political scene. Through this study, it becomes clear that these security companies are commercial entities that aim to achieve profit through their military, consulting, and investment activities. They also serve as arms through which states use these types of companies to achieve their goals. Furthermore, it acknowledges the existence of significant jurisprudential differences in the classification of those working for them.
Keywords: Military and security companies; Wagner Group; Libya; Angola.